Developing consensus on content & format of e-portfolio for MHPE students: a Delphi study - Ambreen Ansar; Yasmeen, Rahila; Mushtaq Rizvi, Robina (Journal of the Pakistan Medical Association, 2022)
Objectives: To build a consensus on portfolio framework for master’s in health professional education students and document programme learning outcomes, tasks for students related to each outcome, and the pieces of evidence regarding the completion of each task. –Continue